Influencia de la comunicación familiar en personas con conducta suicida intervenidos en el hospital. Teófilo Dávila de la ciudad de Machala. - Gálvez Astudillo, Jéssica (2013)
A family that communicates openly and warmly is a family together. The family is the environment where communication reaches its maximum size because it includes the exchange of a whole range of elements unimaginable that can be transmitted at the same time, the human group is more communication in all its forms needs to function properly. Communication is the factor which gives cohesion among family members and makes them feel as a group and to function as such.